LC-MS/MS Based Identification of Antifungal Bioactive Compounds from White Turi (Sesbania grandiflora L.) Stem Bark Extract - Mirah, A. A. Istri; Darmadi, A. A. K.; Suriani, N. L.; Suanda, I.W.; Subrata, I.M. (Universitas Islam Negeri Ar-Raniry, 2026)
White turi (Sesbania grandiflora L.) is a tropical plant belonging to the Fabaceae family that is widely distributed and known for its diverse pharmacological activities. However, the utilization of its stem bark as a source of antifungal agents has been relatively underexplored. This study aimed to identify the phytochemical profile and bioactive compounds of white turi stem bark extract with potential antifungal properties. The sample was extracted using a maceration method with 70% ethanol for 72 hours. Qualitative phytochemical screening was conducted using standard methods, including Mayer, Wagner, Dragendorff, Liebermann–Burchard, and FeCl₃ assays. Further analysis was performed using LC-MS/MS (Agilent 6545 Q-TOF LC/MS System) to identify bioactive compounds. The results revealed the presence of alkaloids, terpenoids, phenolics, tannins, and saponins. LC-MS/MS analysis of the F6 water fraction identified several potential antifungal compounds, including adenine, phenylethyl alcohol, benzenedicarboxylic acid bis (2-ethylhexyl) ester, octadecane, and 2,3-dimethoxybenzaldehyde. These compounds are known to exhibit antifungal mechanisms through disruption of cell membranes, protein denaturation, and inhibition of fungal cellular metabolism. Overall, the findings suggest that white turi stem bark extract has strong potential for development as a natural antifungal agent and as a raw material for plant-based health products. Keyword: Bioactive compounds; natural health products; Sesbania grandiflora L.; LC-MS/MS (Agilent 6545 Q-TOF LC/MS System).